2019
DOI: 10.3390/app9102014
|View full text |Cite
|
Sign up to set email alerts
|

Width Dependent Two-Photon Absorption in Monolayer Black Phosphorus Nanoribbons

Abstract: We analytically study the electronic structures and optical properties of zigzag-edged black phosphorene nanoribbons (ZPNRs) utilizing the tight-binding (TB) Hamiltonian and Kubo formula. By solving the discrete Schordinger equation directly, we obtain the energy spectra and wavefunctions for a N-ZPNR with N number of transverse zigzag atomic chains, and classify the eigenstates according to the lattice symmetry. We then obtain the optical transition selection rule of ZPNRs based on the symmetry analysis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The experimental research activity has been directed to the use of BP layers for ultrafast optical switching and laser pulse generation in optical fibers [27][28][29][30][31][32][33][34][35] (for a review of the field, see [36]). There are also a few theoretical works [37,38,39,[40][41][42] dealing with nonlinear optical properties of phosphorene. In our work [37], it has been shown that the output THG power P(3ω) from undoped monolayer phosphorene strongly depends on the polarization direction of the incident radiation of frequency ω: the P(3ω) is maximum when the radiation is polarized along the 'armchair'(AC) direction, and the P(3ω) vanishes when the radiation is polarized along the 'zigzag' (ZZ) direction (see figure 1, where those directions are chosen as the x and y axes, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental research activity has been directed to the use of BP layers for ultrafast optical switching and laser pulse generation in optical fibers [27][28][29][30][31][32][33][34][35] (for a review of the field, see [36]). There are also a few theoretical works [37,38,39,[40][41][42] dealing with nonlinear optical properties of phosphorene. In our work [37], it has been shown that the output THG power P(3ω) from undoped monolayer phosphorene strongly depends on the polarization direction of the incident radiation of frequency ω: the P(3ω) is maximum when the radiation is polarized along the 'armchair'(AC) direction, and the P(3ω) vanishes when the radiation is polarized along the 'zigzag' (ZZ) direction (see figure 1, where those directions are chosen as the x and y axes, respectively).…”
Section: Introductionmentioning
confidence: 99%